Predictive role of preoperative geriatric nutritional risk index for clinical outcomes in surgical gastric cancer patients: A meta-analysis - Lu, Wei; Shen, Jian; Zou, Dehong; Li, Peng; Liu, Xiaocong; Jian, Yi (Frontiers in Surgery, 2022)
Purpose The association between the preoperative Geriatric Nutritional Risk Index (GNRI) and postoperative short-term and long-term clinical outcomes remains unclear. The aim of this meta-analysis was to identify the predictive role of the preoperative GNRI for postoperative clinical outcomes of gastric cancer patients based on current evidence. Methods Several databases were searched up to July 28, 2022. The primary and secondary outcomes were long-term survival, including overall survival (OS), cancer-specific survival (CSS) and postoperative complications. Meanwhile, the hazard ratios (HRs) and relative risks (RRs) with 95% confidence intervals (CIs) were combined to assess the association of preoperative GNRI with postoperative survival and complications separately. The results Eight studies involving 4,189 patients were included, and they were all from Japan. The pooled results demonstrated that a lower preoperative GNRI was significantly related to worse OS (HR = 1.72, 95% CI: 1.18–2.53, P = 0.005) and CSS (HR = 1.67, 95% CI: 1.20–2.32, P = 0.002). Meanwhile, a lower preoperative GNRI was significantly associated with postoperative complications (RR = 1.97, 95% CI: 1.51–2.58, P < 0.001). Further analysis focusing on elderly patients showed similar results. Conclusion Preoperative GNRI is related to postoperative short-term and long-term clinical outcomes of Japanese gastric cancer patients, and a lower GNRI predicts poorer prognosis.